A computed tomography radiogenomic biomarker predicts microvascular invasion and clinical outcomes in hepatocellular carcinoma. Issue 3 (1st July 2015) - Banerjee, Sudeep; Wang, David S.; Kim, Hyun J.; Sirlin, Claude B.; Chan, Michael G.; Korn, Ronald L.; Rutman, Aaron M.; Siripongsakun, Surachate; Lu, David; Imanbayev, Galym; Kuo, Michael D.
<x xml:space="preserve">Abstract</x> Microvascular invasion (MVI) in hepatocellular carcinoma (HCC) is an independent predictor of poor outcomes subsequent to surgical resection or liver transplantation (LT); however, MVI currently cannot be adequately determined preoperatively. Radiogenomic venous invasion (RVI) is a contrast‐enhanced computed tomography (CECT) biomarker of MVI derived from a 91‐gene HCC "venous invasion" gene expression signature. Preoperative CECTs of 157 HCC patients who underwent surgical resection (N = 72) or LT (N = 85) between 2000 and 2009 at three institutions were evaluated for the presence or absence of RVI. RVI was assessed for its ability to predict MVI and outcomes. Interobserver agreement for scoring RVI was substantial among five radiologists (κ = 0.705; P < 0.001). The diagnostic accuracy, sensitivity, and specificity of RVI in predicting MVI was 89%, 76%, and 94%, respectively. Positive RVI score was associated with lower overall survival (OS) than negative RVI score in the overall cohort (P < 0.001; 48 vs. >147 months), American Joint Committee on Cancer tumor‐node‐metastasis stage II (P < 0.001; 34 vs. >147 months), and in LT patients within Milan criteria (P < 0.001; 69 vs. >147 months). Positive RVI score also portended lower recurrence‐free survival at 3 years versus negative RVI score (P = 0.001; 27% vs. 62%). Conclusion: RVI is a noninvasive radiogenomic biomarker that accurately predicts histological MVI in HCC surgical candidates. Its presence on preoperative CECT is associated with early disease recurrence and poor OS and may be useful for identifying patients less likely to derive a durable benefit from surgical treatment. (Hepatology 2015;62:792–800)